2019
DOI: 10.1002/chem.201901426
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Crystal Structure of a Scarce 1D Polymeric Thorium Peroxo Sulfate

Abstract: The preparation and structural characterization of an original Th peroxo sulfate dihydrate, crystallizing at room temperature in the form of stable 1D polymeric microfibres is described. A combination of laboratory and synchrotron techniques allowed solution of the structure of the Th(O2)(SO4)(H2O)2 compound, which crystallizes in a new structure type in the space group Pna21 of the orthorhombic crystal system. Particularly, the peroxide ligand coordinates to the Th cations in an unusual μ3‐η2:η2:η2 bridging m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…Experimentally, this type of Pu–Pu interaction may be measurable only if the FT range extends beyond 12 Å –1 , according to those calculations (Figure b). This quenching effect is similar to what has been reported for the solid phase on ThSiO 4 nanoparticles and on a polymeric thorium peroxo sulfate structure where the An–An scattering path is annihilated. The same effect was also reported for an iron aqueous solution, where a mixture of monomer and dimer annihilated the Fe–Fe interaction .…”
Section: Resultssupporting
confidence: 88%
“…Experimentally, this type of Pu–Pu interaction may be measurable only if the FT range extends beyond 12 Å –1 , according to those calculations (Figure b). This quenching effect is similar to what has been reported for the solid phase on ThSiO 4 nanoparticles and on a polymeric thorium peroxo sulfate structure where the An–An scattering path is annihilated. The same effect was also reported for an iron aqueous solution, where a mixture of monomer and dimer annihilated the Fe–Fe interaction .…”
Section: Resultssupporting
confidence: 88%
“…The mechanism was evidenced to combine the physical effects of ultrasound, in situ generation of H 2 O 2 and complexation properties of sulfates which further enabled the accumulation of a neo-formed thorium peroxo sulfate with 1D morphology. 216,217 The transposition of this work to nanoscale PuO 2 is an on-going study that demonstrated interesting preliminary results. 123 Moreover, the enhanced reactivity of AnO 2 nanoparticles is particularly interesting since the experimental conditions used for the preparation of several nanostructured PuO 2 samples are similar to the ones used for its industrial preparation dedicated to MOX nuclear fuel.…”
Section: Going Beyond the Fundamental Properties Of Puo 2 Nanoparticlesmentioning
confidence: 87%
“…These two signals fall within the range of typical vibrational bands of free nitrate and coordinated nitrate ligands, but excluding the bidentate chelating fashion [60]. The absorption band ρ r (H 2 O) = 716 cm -1 suggests the presence of coordinated water [57,61], as present in the studtite. The infrared spectra of the other filtered solids of the  series displays similar vibration bands as presented in the Supplementary Information (Figure S5) for the  n°4 and  n°5 powders, confirming the precipitation of studtite and plutonium peroxo-nitrate salt.…”
Section: Infrared and Raman Spectroscopiesmentioning
confidence: 62%
“…Figure 2 displays the IR spectrum of the  n°3 precipitate which evidences the absorption bands of uranyl (ν UO 2 2+ at 897 cm -1 ) and peroxide (ν O 2 2-= 864 cm -1 ) functional groups. The absorption band at ν = 716 cm -1 can be ascribed to the presence of coordinated water molecules [57,61] which are present in studtite. In line with the results of Jere et al [20], no specific band can be associated to peroxide ligand in the thorium peroxide salt.…”
Section: Infrared and Raman Spectroscopiesmentioning
confidence: 99%
See 1 more Smart Citation